Preservation of human vascular tissue and the relevance of temperature: a narrative review - Arbănaşi, Emil-Marian; Chirilă, Traian V. (Frontiers in Bioengineering and Biotechnology, 2026)
This review was intended as a conceptual paper exploring the historical background, general principles, and experimental exploits that have steered meaningful developments in the field of temperature-dependent storage procedures and their impact on the attributes and patency of human vascular tissues assigned for use as grafts in cardiovascular surgery or for research purposes. Attention was focused on advances in the field following a descriptive history of humankind’s progress in developing low-temperature methods to conserve and store perishable goods, in understanding cryptobiotic processes and adopting a scientific approach to preservation of biological matter, and in summarizing the pioneering work of Alexis Carrel and others related specifically to the conservation of blood vessels. Further discussed were the principles of low-temperature preservation methods for cells, tissues, and organs, as well as the range of current techniques. The use of particular techniques for the preservation of human vascular tissues, mainly grafts for surgery, was reviewed, emphasizing the extent of their applications, the range of operating conditions (temperature, cryoprotective agents), and the perceived limitations of diverse procedures. It was concluded that many preservation techniques can be employed successfully for storing human blood vessels, however the deep-subzero temperature methods seem to have been the preferred alternative.